2015
DOI: 10.1155/2015/876923
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Anticoagulation in Patients with Nonvalvular Atrial Fibrillation with Edoxaban Compared to Warfarin in Germany

Abstract: We compared the cost-utility analysis for edoxaban at both doses with that of dabigatran at both doses, rivaroxaban, and apixaban (non vitamin K antagonist oral anticoagulants, NOAC) in a German population. Data of clinical outcome events were taken from edoxaban's ENGAGE-AF, dabigatran's RE-LY, rivaroxaban's ROCKET, and apixaban's ARISTOTLE trials. The base-case analyses of a 65-year-old person with a CHADS2 score >1 gained 0.17 and 0.21 quality-adjusted life years over warfarin for 30 mg od and 60 mg od edox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Patients who might particularly benefit from NOACs include those who cannot take VKAs, have persistently poor TTR (e.g., < 65%) and those taking aspirin for stroke prevention for whom a NOAC may be an option ( Supporting local implementation of NICE guidance on use of the novel (non-Vitamin K antagonist) oral anticoagulants in non-valvular atrial fibrillation, 2015 ). A large reduction in medical cost was mainly driven by reductions in the risks of major bleedings with the NOACs ( Krejczy et al, 2015 ).…”
Section: Cost Effectiveness Of Noacsmentioning
confidence: 99%
“…Patients who might particularly benefit from NOACs include those who cannot take VKAs, have persistently poor TTR (e.g., < 65%) and those taking aspirin for stroke prevention for whom a NOAC may be an option ( Supporting local implementation of NICE guidance on use of the novel (non-Vitamin K antagonist) oral anticoagulants in non-valvular atrial fibrillation, 2015 ). A large reduction in medical cost was mainly driven by reductions in the risks of major bleedings with the NOACs ( Krejczy et al, 2015 ).…”
Section: Cost Effectiveness Of Noacsmentioning
confidence: 99%
“…There have been numerous published cost-effectiveness analyses comparing edoxaban and rivaroxaban with warfarin. 34 , 45 , 49 59 These studies have consistently showed that edoxaban and rivaroxaban are cost-effective relative to warfarin. However, few studies have set out to assess the particular value or cost-effectiveness of one NOAC versus another NOAC, and where such analyses have been conducted (albeit using an indirect comparison approach), there has been substantial inconsistency and contradiction between their findings.…”
Section: Discussionmentioning
confidence: 98%
“…In a study aimed to determine the cost-effectiveness of edoxaban versus warfarin in NVAF patients from the perspective of the Italian healthcare system, edoxaban was costeffective versus warfarin in 92.3% of the simulations at a willingness-to-pay threshold of 25,000 euros per quality-adjusted life year [92]. A study performed in Germany showed that the willingness-to-pay threshold was lowest for 60-mg edoxaban compared with all direct oral anticoagulants and for 30-mg edoxaban compared with dabigatran and rivaroxaban [93]. However, it should be emphasized that the cost-effectiveness of direct oral anticoagulants for stroke prevention in patients with NVAF is highly sensitive to warfarin anticoagulation control (poorer control, more cost-effective) [94].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 98%